2018
DOI: 10.1007/s12602-018-9458-z
|View full text |Cite
|
Sign up to set email alerts
|

Functional Properties of Food Origin Lactobacillus in the Gastrointestinal Ecosystem—In Vitro Study

Abstract: In the current study, the probiotic activity of ten Lactobacillus (Lb.) strains, previously isolated from the traditional Polish fermented vegetable, was characterized. Strains were assessed for adhesion to human intestinal epithelial Caco-2 cells and regulation of selected cytokine production (IL-1β, IL-6, IL-10, IL-23, and TNF-α) by THP-1 macrophages. The effect of tested strains on Caco-2 cell apoptosis was also investigated using a caspase-3 assay. Adhesion capacity was strain-dependent (1.29-8.24% of init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 42 publications
1
16
0
1
Order By: Relevance
“…So, in that study, we postulated that higher IL-10 levels help improve the protection of the upper respiratory tract against mucosal inflammation induced by the marathon [4]. Regarding LcS actions, it was observed that LcS was able to stimulate the immune cells, especially macrophages and dendritic cells, to secrete different cytokines as IL-10, IL-12, IFN-, and TNF-α [31,32,33]. Based on the fact that IL-10 and IL-12 exhibits opposing roles in the regulation of the immune responses, the IL-10/IL-12 ratio has been used as a crucial measure of the balance between the anti-inflammatory and proinflammatory states induced by LcS [34].…”
Section: Discussionmentioning
confidence: 99%
“…So, in that study, we postulated that higher IL-10 levels help improve the protection of the upper respiratory tract against mucosal inflammation induced by the marathon [4]. Regarding LcS actions, it was observed that LcS was able to stimulate the immune cells, especially macrophages and dendritic cells, to secrete different cytokines as IL-10, IL-12, IFN-, and TNF-α [31,32,33]. Based on the fact that IL-10 and IL-12 exhibits opposing roles in the regulation of the immune responses, the IL-10/IL-12 ratio has been used as a crucial measure of the balance between the anti-inflammatory and proinflammatory states induced by LcS [34].…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, contrasting results were described concerning Lactobacillus- mediated apoptosis induction. Some studies demonstrate the ability to prevent pathogen-induced apoptosis (Li et al, 2008; Santos et al, 2016), whereas others state the opposite (Sungur et al, 2017; Zielinska et al, 2018). Interestingly, the timing of the apoptosis induction coincided with the observed shedding.…”
Section: Discussionmentioning
confidence: 99%
“…They can function as a microbial barrier by preventing pathogen binding [ 16 ] and modulation of the immune system [ 17 , 18 ], as well as by the production of inhibitory compounds, such as organic acid, oxygen catabolites, and proteinaceous compounds [ 19 ]. Adhesion ability is strain-dependent, and an evaluation of this characteristic is recommended for the selection of a probiotic [ 19 , 20 ]. Recent research has shown the need to combine in vitro and in vivo approaches with animal models as a preface to human studies in order to decipher probiotic functions and mechanisms of action [ 21 ].…”
Section: Introductionmentioning
confidence: 99%